ANALISIS KAPASITAS FISKAL TUJUH DAERAH PROVINSI BARU - Juli Panglima Saragih (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2016)
Regional autonomy policy that enacted since 2001 has resulted 7 new provinces in Indonesia The consequense is those seven provinces require transfer budget from national government to finance the tasks and authorities assigned as well as development program in the respective provinces. Since it was formed to date, fiscal capacity in 7 provinces expect Banten, are still not able to meet the increased needs of expenditure every year. Its is still very dependent on the fiscal transfer as sources of income because of its own revenue such as PAD still low. This research uses descriptive method-analysis with secondary data analysis that are relevant to the topics discussed, and using the concept of fiscal capacity in the framework of the fiscal decentralization theory. The result of this qualitative research explained that the fiscal capacity index (Indexs kapasitas Fiskal) is high retrieved in 4 Provincies namely Bangka Belitung ; West papua, Riau Provincies and North Maluku. While the index is being retrieved low fiscal capacity index exist on the gorontalo and West Sulawesi provincies. Good fiscal capacity with high index does not guarantee the poor population in the area is reduced, as West Papua and Riau populations that are still relatively lareg in number. In addition , Banten provincies with the PAD is very high compared to other provincies, Still has a large population of the poor. But, overall the transfer fiscal from national government recognized very helpful the fiscal capacity of the those 7 provincies above.